Change in the Properties of Rail Steels during Operation and Reutilization of Rails - Kassym Yelemessov; Dinara Baskanbayeva; Nikita V. Martyushev; Vadim Y. Skeeba; Valeriy E. Gozbenko; Antonina I. Karlina (Metals, 2023)
The paper considers the possibility of reusing previously used railway rails. The analysis is conducted using the standards and operating conditions of the rails of one of the Central Asian states, Kazakhstan, as an example. The operation of these rails causes significant stresses, while the surface layers are strengthened as a result of cold hammering. These phenomena significantly change the physical and mechanical characteristics of rails. As a result, they may not be suitable in terms of parameters for basic use but can be suitable for installation on other tracks. The conducted studies have shown that when the standard service life of the RP65 rail expires, the surface layer is deformed to a depth of up to 300 microns, hardness increases, and internal residual stresses are formed. These changes lead to an increase in the strength properties of the rails. However, at the same time, cracks originate in the surface layer of the rail, thus worsening operational characteristics. The RP65 rails are used under a cyclic load of 700 kN (which is determined by the national standard), withstanding 790,000 cycles. When the load is reduced to 510 kN, these rails can withstand the 2,000,000 cycles required by the standard without failure. Thus, these rails can be reutilized only on non-loaded and non-critical sections.